HR Analytics: Data-Driven Decision Making for Employee Performance Management - Kanchana P, Dr. (South Eastern European Journal of Public Health, 2024)
In the current business environment, Human Resource (HR) Analytics has become a highly useful tool for organizations to make more informed decision with reference to employee performance management based on data derived from the organization. HR analytics plays a critical role in optimizing workforce productivity, improving employee satisfaction and aligning human capital strategies with the organization goals. This paper explores the possibilities of HR analytics in the HR function. With its reliance on advanced data analytics techniques like predictive modeling, machine learning and big data processing; HR analytics equips top decision makers with the ability to notice performance trends, forecast future workforce needs, and to design targeted interventions. The paper presents the evolution of HR analytics from simple metrics measures to high end analytical frameworks for actionable insights. It examines relevant application: Talent acquisition; employee engagement; workforce planning and performance evaluation. Furthermore, it highlights that HR analytics should be a part of organizational decision–making process to obtain strategic outcomes. The second part of this study discusses the challenges of implementing HR analytics, which include data privacy issues, ethical considerations and resistance to change coming from HR practitioners. Challenges in data analysis are explored: So, their methods to overcome them are fostering a data driven culture, investing in analytics training, and compliance to legal and ethical standards. This paper collects existing literature in order to synthesize its finding on the effect of HR analytics in the employee performance management. Finally, the paper concludes that effective implementation of HR analytics optimizes organizational efficiency while affecting an engaged and prosperous workforce. However, the review indicates that HR analytics has great potential to trigger creativity in the domain of human resource management and to spearhead evidence based decision making in the business dynamic context.